Rogue - Steel, Danielle; Lewis, Brian Keith (Grand Haven, MI : Brilliance Audio, 2008)
Blake, the millionaire playboy, and Maxine, the serious professional, have managed to remain friendly despite their divorce. Then Maxine falls in love with another man, just as Blake wants her to join him in a project to help a group of orphans. Could it be that Blake is changing?
Title from container.
Unabridged.
Compact discs.
Duration: 10:00:00.
Director, Lisa Cahn.
Read by Brian Keith Lewis.
Keywords: Divorced parents -- Fiction; Life change events -- Fiction; Audiobooks; Love stories